Characteristics of Paid Malpractice Claims Among Resident Physicians From 2001–2015 in the United States. (15th October 2019) - Glover, McKinley; McGee, Glen W.; Wilkinson, Derek S.; Singh, Harnam; Bolick, Alexis; Betensky, Rebecca A.; Harvey, H. Benjamin; Weinstein, Debra; Schaffer, Adam
Abstract : Purpose: Limited information exists about medical malpractice claims against physicians-in-training. Data on residents' involvement in malpractice actions may inform perceptions about medicolegal liability and influence clinical decision-making at a formative stage. This study aimed to characterize rates and payment amounts of paid malpractice claims on behalf of resident physicians in the United States. Method: Using data from the National Practitioner Data Bank, 1, 248 paid malpractice claims against resident physicians (interns, residents and fellows) 2001–2015, representing 1, 632, 471 residents-years, were analyzed. Temporal trends in overall and specialty-specific paid claim rates, payment amounts, catastrophic (> $1 million) and small (< $100, 000) payments, and other claim characteristics were assessed. Payment amounts were compared to attending physicians during the same time period. Results: The overall paid malpractice claim rate was 0.76 per 1, 000 resident-years from 2001–2015. Among 1, 194 unique residents with paid claims, 95.7% had exactly one claim, while 4.3% had 2 to 4 claims during training. Specialty-specific paid claim rates ranged from 0.12 per 1, 000 resident-years (pathology) to 2.96 (obstetrics/gynecology). Overall paid claim rates decreased by 52% from 2001–2005 to 2011–2015 (95% CI: 0.45, 0.59). Median inflation-adjusted payment amount was $199, 024 (2015 dollars); not significantly different from payments made on behalf of attending physicians during the same period. Proportions of catastrophic (11.2%) and small (33.1%) claims did not significantly change over the study period. Conclusions: From 2001–2015, paid malpractice claim rates on behalf of resident physicians decreased by 52%, while median payment amounts were stable. Resident paid claim rates were lower than attending physicians, while payment amounts were similar.